Aplikasi E-Service Penduduk Berbasis Web pada Desa Sugihan - Army Chella Pusfitasyari; Iwan Setiawan; Nur Aini H (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The internet, which is one of the results of information technology, is an information resource capable of reaching the entire world. The internet is very much needed in carrying out electronic services online for the people of Sugihan Village. The Sugihan Village Office, Rambang District, Muara Enim Regency is one of the agencies in Sugihan Village which has a lot of population data, namely 3,710 people and 947 households (Family Cards), consisting of 1,867 men and 1,843 women. In the previous administrative service process, it required the community to come to the village office directly, but there were obstacles because it took a long time to serve the community because they had to come, queue one by one and wait for the letter to be completed at the village office. While in this study the method used by the author is a qualitative descriptive method which is a research method that utilizes qualitative data and is described descriptively with the aim of describing or describing the results of existing research. The software development method that the author uses is the Prototype model. While the analysis and design tools use UML (Unified Modeling Language) consisting of use case diagrams, class diagrams and activity diagrams. This application can make it easy for people with circumstances or conditions who are unable to come directly to the Sugihan Village office to make letters.